JAK2 Mediates the Regulation of Pept1 Expression by Leptin in the Grass Carp (Ctenopharyngodon idella) Intestine - Luo, Wen-jie; Song, Peng; He, Zhi-min; Cao, Shen-ping; Tang, Jian-zhou; Xu, Wen-qian; Xiong, Ding; Qu, Fu-fa; Zhao, Da-fang; Liu, Zhen; Li, Jian-zhong; Yin, Yu-long (Frontiers in Physiology, 2020)
The oligopeptide transporter (PepT1) is located on the brush-border membrane of the intestinal epithelium and plays an important role in dipeptide and tripeptide absorption from protein digestion. In this study, we cloned and characterized the cDNA sequence of Janus kinase 2 (JAK2) from Ctenopharyngodon idella. The expression patterns of JAK2 in various tissues and developmental stages were characterized by quantitative real-time PCR (qRT-PCR). The mRNA expression levels of JAK2 and PepT1 regulated by leptin in the intestine in vitro and in vivo were also analysed. The cDNA sequences of JAK2 were 3378 bp in length, and the mRNA of JAK2 was broadly expressed in all the selected tissues and embryonic stages of C. idella. In addition, we found that leptin can regulate the intestinal expression of JAK2 and PepT1, and the expression of PepT1 was downregulated by the JAK2 inhibitor AG490 in vivo and in vitro. Furthermore, luciferase experiments showed that overexpression of the JAK2 gene could significantly upregulate the activity of the PepT1 5' regulatory sequence in C. idella. In conclusion, these results may help to elucidate the regulatory effect of the leptin-mediated JAK2 pathway on intestinal PepT1 expression in C. idella and the molecular mechanism of peptide transport by the intestinal transporter PepT1 in fish.